The Relationship Between Knowledge of Occupational Disease and Unfase Action: The Ciparay DTP Health Centre - Yonathan Kristian Yuan Putra; Ivan Ishadi Sofyan; Devi Sri Ayu Kusdiawan (PT Pustaka Cendekia Publisher, 2025)
There are still many PAKS that occur at the DTP Ciparay Health Centre that have been reported to the K3 person in charge, such as COVID-19, Hepatitis B, Measles, Varicella, and Latent TB. The highest number of PAK cases occurred in latent TB disease, affecting 28 workers. Objective: This study aimed to determine the relationship between knowledge of occupational diseases (PAK) and unsafe behaviour. (unsafeaction) the DTP Ciparay health centre. This study is a quantitative study with a cross-sectional design. The population of this study was all workers at the Ciparay Health Centre, namely 71 respondents. The sample of this study was a total sampling. Research data were obtained using a questionnaire instrument. Data were analysed univariately with a frequency distribution table and bivariately with the chi-square test. Shows that the majority of respondents have sufficient knowledge, as many as 48 respondents (67.6%) and almost all respondents behave unsafely in the low category, namely 59 respondents (83.1%) and the results of the bivariate analysis show that there is no significant relationship between knowledge of occupational diseases (PAK) and unsafe behavior. (unsafe action) at the DTP Ciparay health centre with a value of (p > 0.694).Conclusion: There is no significant relationship between knowledge of occupational diseases (PAK) and unsafe behaviour (unsafe action) at the DTP Ciparay health centre, with a value (p>0.694). It is expected that health centres will hold periodic K3 training, namely once every 6 months, for all health centre workers.